2013
DOI: 10.3389/fpls.2013.00533
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal phosphate uptake pathway in maize: vital for growth and cob development on nutrient poor agricultural and greenhouse soils

Abstract: Arbuscular mycorrhizal fungi (AMF) form a mutually beneficial symbiosis with plant roots providing predominantly phosphorus in the form of orthophosphate (Pi) in exchange for plant carbohydrates on low P soils. The goal of this work was to generate molecular-genetic evidence in support of a major impact of the mycorrhizal Pi uptake (MPU) pathway on the productivity of the major crop plant maize under field and controlled conditions. Here we show, that a loss-of-function mutation in the mycorrhiza-specific Pi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
88
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 86 publications
9
88
0
2
Order By: Relevance
“…Arbuscular mycorrhizae fungi (AMFs) can form symbiotic relationships with the vast majority of land plants, enhance biomass and growth rates, improve stress resistance, stimulate mineral nutrients uptake and raise photosynthesis of the infected plants [1][2][3]. For instance, P uptake and growth parameters of cowpea plants were positively influenced by AMFs inoculation under a medium or low P fertilization treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizae fungi (AMFs) can form symbiotic relationships with the vast majority of land plants, enhance biomass and growth rates, improve stress resistance, stimulate mineral nutrients uptake and raise photosynthesis of the infected plants [1][2][3]. For instance, P uptake and growth parameters of cowpea plants were positively influenced by AMFs inoculation under a medium or low P fertilization treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…analyses showed that the symbiotic phosphate transporter ZmPT6, which expresses in mycorrhizal roots and is required for phosphate uptake via AM fungi (Willmann et al 2013), was specifically expressed in the inoculated roots (Fig. 2).…”
Section: Expression Analysis Of Several Genes Involved In Fe Homeostasismentioning
confidence: 99%
“…RNAseq was performed as described previously (Willmann et al, 2013). In brief, .1 mg of molecular grade DNA-free RNA from each sample was used for transcriptome analysis.…”
Section: Rna Transcript Profilingmentioning
confidence: 99%
“…In M. truncatula and rice, loss of function mutations in STR genes resulted in stunted arbuscules (Zhang et al, 2010;Gutjahr et al, 2012), suggesting a role of STR proteins in the transport of metabolites that are essential for a functional root-AMF interaction. Mycorrhiza-specific Pi transporters, such as M. truncatula PHOSPHATE TRANSPORTER4 (MtPT4), Rice PHOSPHATE TRANSPORTER11 (OsPT11), and maize (Zea mays) PHOSPHATE TRANSPORTER1;6 (Pht1;6), localize to arbuscule-containing cells and are indispensable for maintenance of arbuscule function (Javot et al, 2007;Yang et al, 2012;Willmann et al, 2013). Loss-of-function mutants and RNAi lines of MtPT4, OsPT11, and maize pht1;6 mutant led to reduced root colonization with premature degeneration of the arbuscules.…”
mentioning
confidence: 99%